Effectiveness of Artemisia pallens against behavioral depression and impact on monoaminergic and GABAergic systems (Bangladesh Journal of Pharmacology, 2026)
Depression is characterized by decreased monoamine levels (dopamine, noradrenaline, serotonin), gamma-aminobutyric acid (GABA), elevated corticosterone, and dysregulation of the hypothalamic-pituitary-adrenal axis. This study aims to examine the effects of Artemisia pallens against behavioral depression in mice using the tail suspension test. Mice were divided into several groups and received different concentrations of ethyl acetate fractions of A. pallens. The duration of immobility of mice, brain levels of monoamines, GABA, and plasma corticosterone concentration were estimated. Extract (400 mg/kg) significantly (p